Targeted Use of Alcohol-Based Hand Rub on Gloves During Task Dense Periods: One Step Closer to Pathogen Containment by Anesthesia Providers in the Operating Room. (December 2019) - Birnbach, David J.; Thiesen, Taylor C.; McKenty, Nathan T.; Rosen, Lisa F.; Arheart, Kristopher L.; Fitzpatrick, Maureen; Everett-Thomas, Ruth
Abstract : BACKGROUND: Anesthesia providers' hand hygiene practices in the operating room may contribute to the transmission of bacteria. There is a debate, however, over the best approaches for pathogen containment during task dense periods (induction and extubation) of anesthesia care. A novel approach to reducing pathogen spread during these task dense periods is the use of alcohol-based hand rub on gloves when it may be difficult to either change gloves or clean hands. METHODS: To evaluate the impact of alcohol-based hand rub on gloves, we estimated perforation rates of 50 gloves that were worn as pairs by volunteers for 2 hours at a time applying alcohol-based hand rub every 15 minutes (total of 8 alcohol-based hand rub applications per pair of gloves). We also identified perforation rates of 50 new, unused gloves. To evaluate the ability to perform routine anesthesia functions, volunteers were asked to pick up a coin from a table top and document whether the gloves felt normal or sticky at each 15-minute period. RESULTS: Fifty new gloves (not exposed to alcohol-based hand rub) were tested for integrity using the Food and Drug Administration–approved process, and one was found to have a microperforation. Of the 50 gloves that had been applied with alcohol-based hand rub 8 times, no microperforations were identified. All volunteers demonstrated tactile competence by picking up a coin from a table top after 8 alcohol-based hand rub applications; in addition, as the number of alcohol-based hand rub applications progressed, the volunteers reported increased stickiness. CONCLUSIONS: This study suggests that the use of alcohol-based hand rub on commonly used nitrile examination gloves does not compromise glove integrity or hamper the ability to safely perform routine anesthesia functions.